ANALYSIS OF DISTRIBUTION TRANSFORMER LIFE BASED ON LOAD AT PT. PLN (PERSERO) PONTIANAK - Pirniawan, Yoga; Gani, Usman A.; Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2024)
Energy needs in the city of Pontianak are increasingly growing along with population and industrial development. This can be seen from the growth rate of various types of consumer needs, including household, industrial, commercial consumers (shopping centers, entertainment centers, services), educational institutions and offices. A transformer is a static electromagnetic electrical equipment that functions to transfer and change electrical power. Distribution transformers have an important role in distributing electric power in the distribution system. International Electrotechnical Commission (IEC) 534 of 1972 states that if the transformer is loaded stably at its rated power with an ambient temperature of 20 °C, the transformer hot spot temperature will reach 98 °C and the life of the transformer will reach 20 years or 7300 days with losses. normal age 0.0137% per day. The average temperature around the city of Pontianak is 30 °C, so the transformer loading must be adjusted so that the distribution transformer's service life remains normal. There are more than 1000 distribution transformers in Pontianak for residential distribution transformers and industrial distribution transformers. Residential distribution transformers experience a shorter service life because the load usage on the distribution transformer is unstable. This is different from industrial distribution transformers where the usage load is constant. In industrial distribution transformers, there are transformers that are approaching overload with a usage load of 91.88%. The remaining service life is shorter than residential distribution transformers because the load is quite large.